Experimental and numerical investigation of lateral torsional buckling behavior and capacity of welded Q460 beams. (September 2020) - Kang, Lan; Meng, Liuchen; Lin, Yiwei
Abstract: Compared to normal strength steel (NSS), high strength steel (HSS) has many advantages, such as high yield strength, high tensile strength, and high structural reliability. Recently, HSS beams have gradually been employed in practical engineering. In this investigation, eight tests and parametric analysis were carried out to study the lateral torsional buckling (LTB) behavior and capacity of welded Q460 beams. An effective loading system that released the lateral constraint of the loading point was developed. Totally eight tests of welded beams with lateral restraints at two end supports were conducted under a mid-span concentrated force. Among these eight welded beams, one Q235 beam was tested to compare with seven Q460 beams. The flange width-to-thickness ratio changed from 4.6 to 9.6, the web height-to-thickness ratio changed from 28.75 to 47.50, and the beam span was varied from 3 m to 5 m. In addition, a series of parametric analyses considering initial geometric imperfections were performed to evaluate and investigate the effects of key parameters on the LTB behavior of welded Q460 beams. The experimental and numerical results were compared with the LTB curves from Chinese design codes GB50017-2017 and GB50017-201X, Australian code AS4100, and Eurocode 3. The GB50017-201X, AS4100, and Eurocode 3 for general sections underestimate their LTB capacity. The current GB50017-2017 and Eurocode 3 for rolled and equivalent welded sections are unsafe for evaluating the LTB capacity of HSS beams. Modified design equations that are more appropriate for predicting the LTB capacity of welded Q460 beams are presented. Highlights: A total of eight welded Q460 steel beams were tested. An effective test loading system was proposed and employed. Some modified equations based on GB 50017-201X are proposed. Effects of web and flange width-to-thickness ratios are considered dividually. Lateral-torsional buckling capacity of Q460 steel beams is successfully predicted.